PERAN PEMERINTAH DESA TERHADAP KELOMPOK TANI KARYA LESTARI DI DESA TALIKURAN SATU KECAMATAN SONDER KABUPATEN MINAHASA - Imelda ., Manopo; Jenny ., Baroleh; Charles R. Ngangi (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the role of village government towards of karya lestari farmer group in talikuran one village sub-district of sonder district minahasa. The study lasted for 2 (two) months starting from March to April 2017 in Talikuran satu Village Sub-district of Sonder District of Minahasa ranging from preparation, data retrieval, to the preparation or research reports. Data collection methods in this study using primary data and secondary data. Primary data is obtained directly from the source though surveys and interviews using questionnaires to all members of karya lestari farmer groups, while secondary data is obtained directly from institutions related to the research in village government Talikuran one. The result showed that the role of village government towards sustainable farmer group is categorized as excellent with score in the can is 315.